Characterization of an ayurvedic drug (Shilajatwadi Lauha): An approach to standardization - Gupta L.N.; Kumar V.; Kumar N. (My University, 2025)
Shilajatwadi Lauha (SL) is an Ayurvedic Herbo mineral compound formulation used in the treatment of Kshaya and Madhumeha from ancient times. The present study was selected to standardize SL which can be adopted by different Ayurvedic pharmacies for its standardization. For preparation of SL pure Shilajit, Swarna Makshik Bhasma, Shunthi-Marich-Pippali Churna (Trikatu) were taken in equal quantity in mortar and pestle and six times of Lauha Bhasma were added in it and triturated until it becomes fine powder and homogenously mixed. Each of the ingredients was prepared according to the protocols of Ayurvedic texts and by applying Electric muffle furnace as heating device for incineration. To ensure the proper preparation of Bhasmas and other ingredients bhasma parikshas and other tests were employed. After completion of all tests, SL was prepared and subjected for XRD and SEM analysis. XRD study reveals that strongest peak obtained was Fe2O3 and other identified compound was CuS and FeS2 and SEM study shows that the particle size of SL was between 2 to 20 μm. This is the first study in establishing the characterization of SL.